Multidimensional systolic arrays of LMS algorithm adaptive (FIR) digital filters - al-Hilali, Riyad Ali Abd al-Husayn; al-Hashimi, Baqir Abd al-Rasul (Ai-Khawarizmi engineering journal, 2009)
A multidimensional systolic arrays realization of LMS algorithm by a method of mapping regular algorithm onto processor array, are designed. They are based on appropriately selected 1-D systolic array filter that depends on the inner product sum systolic implementation. Various arrays may be derived that exhibit a regular arrangement of the cells (processors) and local interconnection pattern, which are important for VLSI implementation. It reduces latency time and increases the throughput rate in comparison to classical 1-D systolic arrays. The 3-D multilayered array consists of 2-D layers, which are connected with each other only by edges. Such arrays for LMS-based adaptive (FIR) filter may be opposed the fundamental requirements of fast convergence rate in most adaptive filter applications. تتضمن المقالة تصميم منظومات بشكل مصفوفات من المعالجة (الخلايا الانقباضية في جسم الإنسان) لخوارزمية مربع أدنى معدل للمرشح الرقمي و ذلك باستخدام طريقة بتمثيل (تحويل) الخوارزميات الرياضية المنضمة (المرتبة) إلى منظومة من المعالجات المتوازية. بالاعتماد على مصفوفة المعالجات الأحادية الأبعاد للمرشح الرقمي و الذي بدوره يعتمد في عمله على مجموع حاصل ضرب مصفوفة الاخراج. تم اشتقاق مجموعة أنواع من المصفوفات و التي تشكل ترتيب منظم من المعالجات (الخلايا) و طريقة الارتباط الداخلي بين هذه الخلايا و التي تجعلها مهمة الاستخدام في دوائر التكامل القياسية الكبيرة جدا (VLSI). إن الزمن المستغرق للحصول على قيمة واحدة قد انخفض و كذلك معدل الاخراج قد ازداد مقارنة بمصفوفات ذات الأبعاد الأحادية. إن المصفوفة الثلاثية الأبعاد و المتعددة الطبقات تتألف من طبقات ثنائية الأبعاد و التي ترتبط مع بعضها البعض عن طريق الحافات فقط، إن مثل هذه المصفوفات لخوارزمية مربع أدنى معدل للمرشح الرقمي يمكنها تلبية الاحتياجات في تسريع معدل الاقتراب للناتج النهائي في معظم تطبيقات المرشحات الرقمية الملائمة.